A waterproof, low-cost dressing system reduces postoperative wound dressing changes in primary total hip arthroplasty: An efficacy study - Su, Shilong; Wang, Chenggong; Gao, Fawei; Hu, Yihe; Zhong, Da; Lei, Pengfei (Frontiers in Surgery, 2022)
Backgrounds Postoperative wound complication is a major risk factor for the development of Periprosthetic joint infection. We innovatively invented a new dressing system to reduce the occurrence of postoperative wound complications and improve the quality of life of patients after total hip arthroplasty. Methods A total of 120 patients who underwent primary unilateral total hip arthroplasty were enrolled in this study. The data collected included the number of dressing changes, costs of the dressings, postoperative hospital stay, The Visual Analogue Scale (VAS) score, The Harris Hip Score (HHS), ASEPSIS score, The Stony Brook Scar Evaluation Scale (SBSES), wound complications, the frequency of showers and satisfaction. Data were statistically analyzed. Results The average number of dressing changes was 0.74 ±0.46, while the average postoperative hospital stay was 3.67 ±0.97 days. The average cost of the new dressings throughout a treatment cycle was 57.42±15.18 dollars. The VAS score decreased from 5.63±1.09 before the operation to 0.88±0.54 one month after the operation. The HHS score increased from 70.18±7.84 before the operation to 80.36±4.08 one month after the operation. The results of the four indexes of the ASEPSIS score were all 0. The SBSES score was 3.55±0.61 at two weeks after the operation, and 4.38±0.71 at one month after the operation. No wound complications were recorded until one month after the operation when the satisfaction rate was 92.53 ±3.62%. Conclusion In this study, we have invented a new dressing system for surgical wounds after total hip arthroplasty and confirmed its efficacy. Chinese Clinical Trial Registry: ChiCTR2000033822, Registered 13/ June/2020